Small talk as work talk: Enacting the patient-centered approach in nurse-practitioner-patient visits. (1st November 2017) - Defibaugh, Staci
Abstract : Small talk in medical visits has received ample attention; however, small talk that occurs at the close of a medical visit has not been explored. Small talk, with its focus on relational work, is an important aspect of medical care, particularly so considering the current focus in the US on the patient-centered approach and the desire to construct positive provider– patient relationships, which have been shown to contribute to higher patient satisfaction and better health outcomes. Therefore, even small talk that is unrelated to the transactional aspect of the medical visit in fact serves an important function. In this article, I analyze small talk exchanges between nurse practitioners (NPs) and their patients which occur after the transactional work of the visit is completed. I focus on two exchanges which highlight different interactional goals. I argue that these examples illustrate a willingness on the part of all participants to extend the visit solely for the purpose of constructing positive provider–patient relationships. Furthermore, because exchanges occur after the 'work' of the visit has been completed, they have the potential to construct positive relationships that extend beyond the individual visit.